Profile of Teacher Decision-Making in Designing Mathematical Tasks Based on Teaching Experience - Taufiq Taufiq; Mega Teguh Budiarto; Tatag Yuli Eko Siswono; Ahmad Wachidul Kohar (Indonesia Emerging Literacy Education, 2023)
Objective: This research aims to describe the decision-making profile of mathematics teachers in designing mathematical assignments based on teaching experience. Method: The subjects of this study were mathematics teachers in junior high school education units with a bachelor's degree in mathematics education, including one senior teacher (ST) and one novice teacher (NT). The researcher used a task sheet for making a mathematical task design (TSMTD) and an interview guide as instruments for data collection. Results: The results showed that both novice and senior teachers identified problems by mentioning known information, but novice teachers tended to modify textbook assignments as materials for designing questions. In collecting information, beginner and senior teachers compared ideas from previous experiences, but senior teachers considered the context of the questions to be designed. Beginner teachers submitted problems by raising the theme of comparing values and transforming values with different resolution processes, while senior teachers considered several contexts and chose multiple alternative solutions. Both beginner and senior teachers checked all the questions designed and assessed the feasibility of the solutions generated from the task. Novelty: This research contributes to the understanding of the decision-making profile of mathematics teachers in designing assignments based on their teaching experience, highlighting the differences between novice and senior teachers in terms of problem identification, information collection, problem submission, and checking of designed questions.